Proceedings of the 2006 International Workshop on Global Software Development for the Practitioner 2006
DOI: 10.1145/1138506.1138525
|View full text |Cite
|
Sign up to set email alerts
|

Distributed development in an intra-national, intra-organisational context

Abstract: This paper reports from a study investigating distributed development in an intra-national and intra-organisational company context. The study gives an insight into issues related to, and strategies for successful distributed development seen in a project at Ericsson Microwave Systems. We conclude that regular, informal communication is the single most important factor for success in the project, with important roles in improving motivation and coordination. The leader's role in setting clear and transparent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
2
10
0
4
Order By: Relevance
“…We take this as evidence that clear distinctions of leadership style between distributed and collocated teams is blurring, as has been indicated in related literature (Lindqvist et al, 2006). And while leaders from our study do play a role in their organization's teams, this role is not readily evident or markedly salient.…”
Section: Discussion and Future Researchsupporting
confidence: 61%
“…We take this as evidence that clear distinctions of leadership style between distributed and collocated teams is blurring, as has been indicated in related literature (Lindqvist et al, 2006). And while leaders from our study do play a role in their organization's teams, this role is not readily evident or markedly salient.…”
Section: Discussion and Future Researchsupporting
confidence: 61%
“…The importance of trust in distributed software engineering teams has been recognized by several researchers [17,32,10,21,37]. Their findings reinforced the critical role trust plays in performance and further found that trust needs to be established early during team evolution by meeting team expectations.…”
Section: Trust In Contextmentioning
confidence: 88%
“…As a result, decreases in productivity or increases in the number of defects have been reported. Their causes include communication problems between sites , insufficient knowledge at one of the sites , mistrust between sites , or decreased workforce motivation because of the fear of job loss . Therefore, they represent a set of GSD‐specific project risks that might be relevant in addition to the typical project risks.…”
Section: Introductionmentioning
confidence: 99%